The role of the national language and the historical legacy in nurturing national integration among Malaysians - Che Rodi, Rozita; Musa, Hashim (Human Resource Management Academic Research Society, 2023)
The questions of national integration and unity are critical issues in Malaysia in the effort to promote national development, since Malaysia is a heterogeneous nation in terms of race, culture, creed and language. Without integration and unity national development programmes will face a lot of difficulties, and in fact bound to be doomed. In this article discussions will focus on the concepts of Malaysian nation state, national integration and unity, and will propose three strategies to develop national integration and patriotism, namely 1) empowering Malay language as the language of education, higher learning and integration, 2) instilling deep understanding of the historical legacy in the formation of Malaysian nation state, 3) instilling strong spirit of patriotism that is love towards Malaysia and cultivate a sense of pride, belonging and commitment amongst citizens towards Malaysia as their country of birth and their homeland.